Haematogical and biochemical proflies of rabbits fed pelleted and non pelleted maize substituted sweet potato root diets (2011)
Unpeeled, sliced sun-dried sweet potato roots were milled and replaced with maize at 0, 25. 50, 75 and 100% levels in the diets rabbits. Fifty mongrel rabbits aged between 8-10 weeks average body weight of 650.25A0.33g were randomly allotted to the ten diets with five rabbits per diet. A group of five diets were fed in meal form while a second group was fed in pelleted form. The rabbits were fed and given water ad libitum for 10 weeks. At the end of the tenth week blood samples were collected from the marginal ear vein for haematological and serum profiles. Except for PCV and MCHC values of rabbits fed non pelleted total replacement of maize with sweet potato all the haematological and biochemical indices did not show any appreciable effects.